Pigmented purpura and cutaneous vascular occlusion syndromes - Ana Cecilia Lamadrid-Zertuche; Verónica Garza-Rodríguez; Jorge de Jesús Ocampo-Candiani (Sociedade Brasileira de Dermatologia, 2018)
Abstract: Purpura is defined as a visible hemorrhage in the skin or mucosa, which is not evanescent upon pressure. Proper classification allows a better patient approach due to its multiple diagnoses. Purpuras can be categorized by size, morphology, and other characteristics. The course varies according to the etiology, as do the diagnostic approach and treatment. This review discusses pigmented purpuras and some cutaneous vascular occlusion syndromes.